(untitled) - Belcher, Richard William

Tectonostratigraphic evolution of the Swartland region and aspects of orogenic lode-gold mineralisation in the Pan-African Saldania Belt, Western Cape, South Africa (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2003.